Understanding the Early Adjustment Experiences of Undergraduate Distance Education Students in South Africa - Mittelmeier, Jenna; Rogaten, Jekaterina; Long, Dianne; Dalu, Mwazvita; Gunter, Ashley; Prinsloo, Paul; Rienties, Bart (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
Much research in face-to-face contexts outlines the importance of early adjustment on students’ higher education experiences. However, few studies have replicated this research in distance learning contexts to unpack the early multifaceted adjustments associated with studying in absence of a physical campus. This is particularly needed from a Global South perspective, where countries like South Africa have become regional hubs for distance learners. To explore distance learners’ adjustment experiences, this study analysed results from a Student Adaptation to College Questionnaire (SACQ) with 320 distance learners at the University of South Africa, mixed with qualitative thematic analysis of open-ended questions. The results outlined key factors that impact distance learning experiences for students in South Africa, including demographic variables, class, language, and access to resources. These findings, compared with similar work in face-to-face contexts, suggest areas in need of additional support from distance education providers in South Africa and beyond.